Alternative energy learning with stem approaches to increase student’s interest and creativity - Rahma Aisyah; Elly Sukmanasa; Didit Ardianto (Institute of Computer Science (IOCS), 2026)
Traditional elementary science instruction often relies on conventional teaching methods that inadequately contextualize abstract concepts, resulting in low student engagement, limited interest, and reduced creativity in learning energy transformation. This study proposes an integrated Science, Technology, Engineering, and Mathematics (STEM) approach adapted for fourth-grade students through a hands-on mini waterwheel project. A quasi-experimental pretest–posttest control group design was employed involving 50 students divided into an experimental group (integrated STEM) and a control group (standard Inquiry). Data were collected using learning achievement tests, questionnaires, and creativity assessment rubrics, and analyzed through independent sample t-tests and linear regression. The results demonstrate that the STEM approach significantly outperformed the conventional inquiry model in enhancing student creativity (t = 4.454, p < 0.05) and increasing learning interest. In addition, a strong positive correlation was identified between learning interest and creativity (r = 0.694), with learning interest contributing 73.3% to students' creative performance. These findings indicate that integrating STEM into elementary science instruction effectively transforms abstract scientific concepts into meaningful engineering experiences while fostering creativity and motivation. Therefore, the proposed instructional model provides a practical framework for elementary educators to systematically integrate interdisciplinary problem-solving into science learning, thereby promoting critical thinking, creativity, and adaptive skills from an early age.